2023
DOI: 10.3390/cancers15061754
|View full text |Cite
|
Sign up to set email alerts
|

Social Support in a Cancer Patient-Informal Caregiver Dyad: A Scoping Review

Abstract: Social support that includes promoting healthy behaviours throughout the oncology pathway, from diagnosis to treatment to survival, can leverage existing support networks and improve the health of patients and family members in supportive roles. This scoping review aimed to identify and summarise the impact of social support on the patient-informal caregiver relationship during cancer treatment. Inclusion criteria were related to a high focus on dyadic cancer patient-informal caregiver relationships, consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Self-management competency are a key variable in improving the health status and quality of life of cancer patients [41]. Multiple regression analysis in this study also found that PICC self-management competency (β= 0.169, p < 0.001) had a signi cant effect on upper arm exercise self-e cacy in cancer patients with PICC, higher self-management ability was associated with higher upper arm exercise selfe cacy.…”
Section: Picc Competency In Uence Upper Arm Exercise Self-e Cacy In C...supporting
confidence: 64%
“…Self-management competency are a key variable in improving the health status and quality of life of cancer patients [41]. Multiple regression analysis in this study also found that PICC self-management competency (β= 0.169, p < 0.001) had a signi cant effect on upper arm exercise self-e cacy in cancer patients with PICC, higher self-management ability was associated with higher upper arm exercise selfe cacy.…”
Section: Picc Competency In Uence Upper Arm Exercise Self-e Cacy In C...supporting
confidence: 64%
“…Hope may influence symptom burden, improving their quality of life [13,42]. Among the environmental factors, social support is essential for cancer patients [43]. Chen et al found that social support and cancer treatment were China's hottest topics in cancer communication [44].…”
Section: Evaluate the Effectmentioning
confidence: 99%
“…Similar suggestions have been provided in a previous report indicating that social support—including promotion of healthy behaviors throughout the oncology pathway, from diagnosis to treatment to survival—can improve the health of patients and family members in supportive roles. 24 …”
Section: Discussionmentioning
confidence: 99%